HPLC for identification of compounds in diluted phosphoric (H3PO4) treatment in cellulosic ethanol production - Horst, Diogo J.; Petter, Rodolfo R. H.; Wagner, Theodoro M.; Vieira, Rogério de A. (Avances en Energías Renovables y Medio Ambiente - AVERMA, 2022)
This paper reports an ethanol production by using cellulosic residues also using a method for identification of the compounds dispersed in diluted phosphoric hydrolysate treatment. Twelve different wood chips collected in southern regions of Brazil were used. High performance liquid chromatography (HPLC) employing analytical proton-exchange technique was used. The fermentation ability plus ethanol yields by using Saccharomyces cerevisiae were investigated. Standard compounds identified in analysis were: fructose, lactic acid, acetic acid, glycerol, glucose and ethanol. The yeast showed good ethanol productivities in ranges between: 3.11 g/L/h in Myroxylon peruiferum and 1.74 g/L/h in Nectandra lanceolata, respectively, after the essays. The waste materials showed similar efficiency in ethanol production. This paper contributes to the sustainable biofuels production through the process monitoring and optimization, contributing to the renewable energies through the engineering of production.